Birth sequence and its effects on litter size - J D Wheat; M S Suba; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1982)
Average farrowing interval and duration were 15.8 and 143.8 minutes for 1766 pigs born in 169 litters. Pigs born later in the litter were larger (r=.43) at birth. The correlation was -.14 between farrowing interval, average time between the birth of pigs within the litter, and litter 21-day weight. Sixteen pigs were classified as mummies and their birth sequences ranged from 1 to 15 with an average of 6.5. In 53.5 percent of the litters, the first pig born was a gilt and in 18.4 percent of the litters the first pig born was the largest in the litter. However, the first pig born was the smallest in the litter in 13.5 percent of the litters. The last pig in the litter was the smallest pig in 8.5 percent and largest in 16.3 percent of the litters. Pigs dead at birth, but not classified as mummies, ranged in birth order from 1 to 15 and had an average rank of 7.5. Among pigs dead at birth, 67 percent were boars.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Birth sequence; Litter size